A Broadband Vibration-Based Energy Harvester Using an Array of Piezoelectric Beams Connected by Springs - V. Meruane; K. Pichara (Shock and Vibration)
Piezoelectric cantilevered beams have been widely used as vibration-based energy harvesters. Nevertheless, these devices have a narrow frequency band and if the excitation is slightly different there is a significant drop in the level of power generated. To handle this problem, the present investigation proposes the use of an array of piezoelectric cantilevered beams connected by springs as a broadband vibration-based energy harvester. The equations for the voltage and power output of the system are derived based on the analytical solution of the piezoelectric cantilevered energy harvester with Euler-Bernoulli beam assumptions. To study the advantages and disadvantages of the proposed system, the results are compared with those of an array of disconnected beams (with no springs). The analytical model is validated with experimental measurements of three bimorph beams with and without springs. The results show that connecting the array of beams with springs allows increasing the frequency band of operation and increasing the amount of power generated.